Gait analysis of patients subjected to the atrophic mandible augmentation with Iliac bone graft - Temelli, Yener; Arslan, Yunus Ziya; Cansız, Erol; Karabulut, Derya; Doğru, Suzan Cansel; AKALAN, NAZİF EKİN (HINDAWI LTD, ADAM HOUSE, 3RD FLR, 1 FITZROY SQ, LONDON, W1T 5HF, ENGLAND, 2019)
In this study, we aimed to quantitatively monitor and describe the gait functions of patients, who underwent iliac crest bone grafting in atrophic jaw augmentation operation, by taking into account the alterations of gait parameters and muscle forces in the early recovery course. To do so, temporospatial and kinematic gait parameters of ten patients during pre- and postoperative periods were recorded, and forces of the gluteus medius, gluteus maximus, and iliacus muscles were calculated. Three postoperative periods were specified as one week (post-op1), two weeks (post-op2), and three weeks (post-op3) after the surgery. Restoring process of the gait patterns was comparatively evaluated by analyzing the gait parameters and muscle forces for pre- and postoperative periods. Temporospatial and kinematic parameters of post-op3 were closer to those obtained in pre-op than those in post-op1 and post-op2 (p<0.05). Muscle forces calculated in post-op3 showed the best agreement with those in pre-op among the postoperative periods in terms of both magnitude and correlation (p<0.05). In conclusion, the patients began to regain their preoperative gait characteristics from the second week after surgery, but complete recovery in gait was observed three weeks after the surgery.

Bu çalışmada, atrofik çene büyütme operasyonlarında iliak kret kemik grefti yapılan hastaların yürüyüş fonksiyonlarını kantitatif olarak izlemeyi ve tarif etmeyi amaçladık, erken iyileşme seyrinde yürüyüş parametreleri ve kas kuvvetlerindeki değişiklikleri göz önünde bulundurarak. Bunu yapmak için ameliyat öncesi ve sonrası on hastanın temporospatial ve kinematik yürüme parametreleri kaydedildi ve gluteus medius, gluteus maximus ve iliacus kaslarının kuvvetleri hesaplandı. Ameliyat sonrası üç dönem ameliyat sonrası bir hafta (ameliyat sonrası1), iki hafta (ameliyat sonrası2) ve ameliyat sonrası üç hafta (ameliyat sonrası3) olarak belirlendi. Yürüyüş paternlerinin restorasyon süreci, yürüyüş parametreleri ve kas kuvvetleri ameliyat öncesi ve sonrası dönemler için analiz edilerek karşılaştırıldı. Post-op3'ün zamansal ve kinematik parametreleri, ameliyat öncesi elde edilenlere ameliyat sonrası ve ameliyat sonrası2'dekinden daha yakındı (p <0.05). Ameliyat sonrası hesaplanan kas kuvvetleri, ameliyat sonrası dönemlerde ameliyat öncesi olanlarla hem büyüklük hem de korelasyon açısından en iyi uyumu gösterdi (p <0.05). Sonuç olarak, hastalar ameliyat sonrası ikinci haftadan itibaren preoperatif yürüyüş özelliklerini geri kazanmaya başladılar ancak ameliyattan üç hafta sonra yürüyüşlerde tam iyileşme gözlendi.
Keywords: Crest; Morbıdıty; Anterıor; Donor; Complications; Harvest; Force